Patients’ satisfaction with services provided by family physicians at the Comprehensive Healthcare Centers in Northern Jordan - Hadeel B. Heilat; Muntaha K. Gharaibeh; Wanas M. Shtaiyat; Raghad S. Gharaibeh; Ayah M. Ananbeh; Manar J. Baniyaseen; Shahd M. Alsharaydeh; Aya B. Alqawaba’h; Emad A. Alzu’bi; Nour G. Amayreh; Reem R. Aldawagreh (Journal of Family and Community Medicine)
BACKGROUND: Patient satisfaction is a paramount measure of the quality of healthcare system, particularly in the practice of family medicine. The study aimed to assess patients’ satisfaction with services provided by family physicians (FPs) at Comprehensive Healthcare Centers (CHCCs) in Northern Jordan. MATERIALS AND METHODS: A cross-sectional study was conducted at 11 CHCCs in Northern Jordan between July and October 2023. A convenient sample of 367 patients, both males and females over the age of 18 years, was selected. Participants were requested to complete the Arabic version of the Consultation Satisfaction Questionnaire (CSQ). Mean and standard deviation calculated for continuous variables, and frequencies and percentages for categorical variables. Multivariable logistic regression analysis yielded factors related to patients’ satisfaction with family physician. RESULTS: The mean score of patients’ satisfaction was 55.63 ± 12.15. The highest mean satisfaction scores were reported for the “professional care” provided by the FP (72.41 ± 15.9), followed by the “depth of relationship and the length of consultation” with the FP, respectively. Patients who had a reference health center if needed (P < 0.002), had health insurance (P < 0.05), patient’s privacy (P < 0.027), and waiting time < 20 min to see the FP (P < 0.001) were all positively associated with the status of patients’ satisfaction. Logistic regression final model included only two factors, waiting time < 20 minutes and having a reference health center. CONCLUSION: The study reveals moderate patient satisfaction with care provided by FP. The moderate satisfaction is attributed to good care provided by FP and the least to the length of consultation. The predictors of satisfaction are the waiting time to see FP and the availability of a reference health center. Study has implications for the health care system in Jordan, as regards the strengthening of the health information system to incorporate policies on appointments, quality of consultation times, and waiting times.